Morphology of cells undergoing epithelial mesenchymal transition in microinvasive and early invasive oral squamous cell carcinom a – a light microscopic study - Kalele, Ketki; Bhondekar, Vaishnavi; Dongare, Shruti; Khan, Wasim; Shelotkar, Ashwini; Badukale, Kaustubh; Damare, Kanchan (Polish Journal of Pathology, 2022)
The present study focuses on identification of cancer attributes of epithelial mesenchymal transition (EMT) at the earliest possible stage (microinvasion) under a light microscope by using hematoxylin and eosin stains, making it feasible for researchers to investigate such cases with ease without the use of extensive setups. The present study is the first in the English literature to define EMT features in micro-invasive and early invasive oral squamous cell carcinoma (OSCC) under a light microscope. This is a retrospective study of histological sections of 43 cases of OSCC from the Department of Oral Pathology and Microbiology. The data collected were later statistically analyzed. A total of 11 micro-invasive and 32 early invasive OSCC cases were assessed for core features of EMT. The predominant feature defining EMT found was dense inflammatory infiltrate in both microinvasive (91%) and early invasive OSCC (88%) followed by cell individualization in 82% of microinvasive and 75% of early invasive OSCC, which was then followed by other features. Reporting EMT in histopathological reports on a daily basis can aid in early diagnosis of OSCC as well as understanding carcinogenesis in early stages. Thereby, inclusion of EMT targeting therapeutics in early stages of OSCC can significantly alter the prognosis of cancer.